2021
DOI: 10.3389/fonc.2021.645328
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Radiation Techniques for Comprehensive Regional Nodal Radiation Therapy for Left-Sided Breast Cancer: A Treatment Planning Study

Abstract: PurposeHow modern cardiac sparing techniques and beam delivery systems using advanced x-ray and proton beam therapy (PBT) can reduce incidental radiation exposure doses to cardiac and pulmonary organs individually or in any combination is poorly investigated.MethodsAmong 15 patients with left-sided breast cancer, partial wide tangential 3D-conformal radiotherapy (3DCRT) delivered in conventional fractionation (CF) or hypofractionated (HF) schedules; PBT delivered in a CF schedule; and volumetric modulated arc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This outcome is attributed to the excellent depth-dose distributions of PBT, allowing for a substantial reduction in OAR doses while preserving target coverage. Prior research has consistently reported that proton therapy offers significant advantages in sparing the heart and lungs compared to XRT [25][26][27][28] . Ischemic heart disease can persist for up to 20 years after radiation exposure, and there is a proportional increase in coronary events with the mean dose to the heart, without a clear cutoff value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome is attributed to the excellent depth-dose distributions of PBT, allowing for a substantial reduction in OAR doses while preserving target coverage. Prior research has consistently reported that proton therapy offers significant advantages in sparing the heart and lungs compared to XRT [25][26][27][28] . Ischemic heart disease can persist for up to 20 years after radiation exposure, and there is a proportional increase in coronary events with the mean dose to the heart, without a clear cutoff value.…”
Section: Discussionmentioning
confidence: 99%
“…robustness, has been documented 23,24 . Studies have examined dosimetric variations among different treatment techniques to mitigate long-term radiation side effects in breast cancer radiation therapy and have assessed the effects of CTV size, organs at risk (OARs), target distances, treatment positions, and other factors on treatment planning [25][26][27][28][29][30][31][32] . However, there has been limited focus on arc-delivery PBT, including CIRT.…”
mentioning
confidence: 99%
“…Furthermore, various in silico WBI planning trials described contralateral breast mean doses for different scenarios (free breathing, breath hold, various field geometrics etc.) between 0.32 and 4.80 Gy [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In the present analysis, the mean dose to the contralateral breast was comparatively low at 0.80 Gy for all patients after WBI.…”
Section: Discussionmentioning
confidence: 99%
“…As information on dosimetry becomes more evident, efforts have been made to develop more sophisticated planning techniques to achieve improved dosimetry than would otherwise be expected from traditional techniques. With volume-based planning, use of partially wide tangents in hypofractionated radiotherapy yielded ipsilateral lung V20 values of 41% in a treatment planning study [ 26 ]. In our study, with the use of 3D-CRT and volume-based planning, we were able to achieve adequate target coverage and acceptable heart doses although with a slightly higher ipsilateral lung dose than intended.…”
Section: Discussionmentioning
confidence: 99%